STEAM-based learning on renewable energy topics in high school physics for grade X - Lukma, Hazairin; Lukma, Hazairin Nikmatul (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2025)
This study aims to examine the effectiveness of the STEAM-based learning approach (Science, Technology, Engineering, Art, and Mathematics) on the topic of renewable energy in improving high school students' conceptual understanding. Using an embedded mixed methods design, quantitative data were collected through pretests and post-tests, while qualitative data were obtained through observations, interviews, and questionnaires. The research subjects consisted of 36 tenth-grade students at SMAN 2 Blitar. The analysis results showed a significant improvement in students' conceptual understanding scores following the implementation of STEAM-based learning. Additionally, students demonstrated increased engagement, motivation, and creativity, as well as critical and collaborative thinking skills. However, this study also revealed several challenges in implementing STEAM, such as time constraints, teacher preparedness, assessment issues, and limited facilities and resources. These findings confirm that although STEAM is effective in enhancing the quality of learning, its implementation requires systematic planning, adequate teacher training, and sufficient infrastructure support to optimize student learning outcomes.